A prototype of 3D-printed permanent magnet generator for low power applications - Chaiyong Soemphol; Adisorn Nuan-on; Peeradapath Parametpisit (Institute of Advanced Engineering and Science, 2022)
Recently, there has been a growing interest in the field of using 3D-printing technology for electrical machine manufacturing. However, almost research works have been done majorly on the 3D-printing technology of individual working parts for various electrical machines. This research presents a study of design, fabrication and testing of the protopype of permanent magnet generator using 3D-printing technology. The major parts of proposed generator are fabricated though 3D-printed materials. The stator winding of designed generator consists of 12 slots. The stator coil is designed to have 250 turns per slot and 12 pieces of neodymium magnets are used in to generate magnetic field in the rotor core. The prototype generator is tested under different condition; no-load and loaded-test. The experimental have been shown that in the no-load condition, this generator is able to generate output voltage of 3.3-64.5 V, when rotated at speed of 100-2,500 rpm. In the loaded-test, the output voltage and output current are also generated. Furthermore, it can be seen that a proposed generator can generate the output power of 4,245.28 mW, when rotated at speed of 2,500 rpm.